ORGANIZATION OF COMPREHENSIVE ASSESSMENT OF CHILDREN’S DEVELOPMENT: A PRACTICE-ORIENTED APPROACH - Matveieva, Nataliia (Mountain School of Ukrainian Carpaty, 2022)
The article describes the regulatory and legal foundations of the organization and implementation of a comprehensive assessment of the development of children of different ages. The purpose, content, main tasks, directions of comprehensive assessment of the development of children of different ages are analyzed. The functions of the specialists of the inclusive resource center are characterized; the specifics of conducting a comprehensive assessment of children's development according to their type of impairment and individual characteristics are disclosed. The specifics of the practical activities of the team of specialists are defined; the specifics of the work of a speech therapist teacher, a special education teacher, a physical therapy teacher (rehabilitator), and a practical psychologist are highlighted. The main principles on which the professional activity of specialists in the process of comprehensive assessment of children's development is based are established and characterized. Stages of comprehensive assessment and directions of individualized work with a child with developmental disorders are delineated. It was noted that the practical activity of the center's specialists after the completion of the comprehensive assessment has its logical continuation, which is expressed in the consultation of teachers of preschool, general secondary, vocational and technical education institutions on the organization of inclusive education. Emphasis is placed on the content of methodological assistance of specialists to pedagogical workers, parents or legal representatives of children with special educational needs. The forms of practical work of specialists in providing psychological-pedagogical and correctional-developmental services to children with developmental disabilities, organization of parents' consultations regarding the choice of a network of educational institutions are disclosed and analyzed. Factors influencing the quality of comprehensive assessment of children's development are emphasized, namely: taking into account the results of observing the child, his environment and conditions of development, psychological and pedagogical characteristics, notebooks, drawings and creative works, documents of additional examinations. The types, forms and methods of work of each of the specialists, areas of comprehensive assessment, tasks and predicted results where analyzed.